Al-Saja’ Al-Qur’an ‘Inda Imam al- Baqillani (Dirasah Tahliliyah Naqdiyah) - Farahanim Mohd Esa; Nadwah Daud (Studia Quranika, 2020)
This Article discusses the arguments that announced by Imam al-Baqillani to deny the existance of saja’ in the Holy qur’an. Imam al-Baqillani stated four arguments in this regard. The first, saja’ is created by shaman. Saja’ is one of human speech type that means relied on the word. Saja’ has unperfect measure. The second, the writer discusses the issue of saja’ in the holy Quran. It assumed that shaman’s creation are compositional and faked. However, the principle of saja’ in Al qur’an is on the contrary. It was because that the decree of Allah is not human saying.It was miracle in words and meaning. Saja’, in Al-Qur’an, rhetorically,aimed to strengthen the meaning carried. This character is definitely different with the arabic poetry with the unperfect saja’.